Pengaruh Metode Drill untuk Meningkatkan Kemampuan Membaca Al-Qur'an Siswa Kelas V: Studi Kasus di Madrasah Ibtidaiyyah Roudlotul Ulum Pilang Wonoayu Sidoarjo - Jumadi Jumadi; Moh. Irfan; Shofwatal Qolbiyyah (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2025)
This study aims to find the effect of the Drill method to improve the ability to read the Qur'an of Class V students in Madrasah Ibtidaiyyah Roudlotul Ulum Pilang Wonoayu Sidoarjo. This descriptive quantitative research, with the data collection method carried out using a reading test Al-Qur’an. The data analysis technique used is descriptive and inferential statistical analysis. The results of the inferential statistical analysis in terms of increasing the reading of the Qur'an by using the T-test formula can be known that t count = 11.04 and t table = 2,045, then t count> t table or 11.04> 2,045, so it can be concluded that HA is accepted and H0 is rejected. This means that the influence of the Drill method in increasing the reading of the Koran in students of class V MI Roudlotul Ulum Pilang Wonoayu Sidoarjo. Keywords : Drill method, The ability to Read the Koran